Pengelolaan Sampah Mandiri Berbasis Pemberdayaan Ekonomi dan Lingkungan Masyarakat - Yuyun Wahyuni; Nunuk Dwi Garwanti; Dwi Hariyanti (Humanism: Journal of Community Empowerment (HJCE), 2019)
Thin Community Service Program is aimed to manage organic and non-organic waste, based on social capability in the community. This program is also designed to empower the economy level of local people. There are three methods used in this program : (i) training in making souvenirs and crafting based on waste materials, built the warehouse for waste and creating the composter to handle organic waste. Based on time schedule, the training already here done twice and produced artificial flowers and bags from plastic waste. The both then is packaged and ready to be coomercialized. The warehouse for the waste also already have made from galvalum materials, included the roof one door and paving block floors. Twenty three composter also have distributed to the program participants. The composter already used by them to manage organic waste and produced vegetebles fertilizer. Key Words: Waste Management, Economy Empowerment, Community Environments